Evaluating Sexual Dimorphism of the Muscle Spindles and Intrafusal Muscle Fibers in the Medial Gastrocnemius of Male and Female Rats - Magdalena Gartych; Hanna Jackowiak; Dorota Bukowska; Jan Celichowski (Frontiers Media S.A., 2021)
This study sought to investigate the sexual dimorphism of muscle spindles in rat medial gastrocnemius muscle. The muscles were cut transversely into 5-10 and 20 μm thick serial sections and the number, density, and morphometric properties of the muscle spindles were determined. There was no significant difference (p > 0.05) in the number of muscle spindles of male (14.45 ± 2.77) and female (15.00 ± 3.13) rats. Muscle mass was 38.89% higher in males (1.08 vs. 0.66 g in females), making the density of these receptors significantly higher (p < 0.01) in females (approximately one spindle per 51.14 mg muscle mass vs. one per 79.91 mg in males). There were no significant differences between the morphometric properties of intrafusal muscle fibers or muscle spindles in male and female rats (p > 0.05): 5.16 ± 2.43 and 5.37 ± 2.27 μm for male and female intrafusal muscle fiber diameter, respectively; 5.57 ± 2.20 and 5.60 ± 2.16 μm for male and female intrafusal muscle fiber number, respectively; 25.85 ± 10.04 and 25.30 ± 9.96 μm for male and female shorter muscle spindle diameter, respectively; and 48.99 ± 20.73 and 43.97 ± 16.96 μm for male and female longer muscle spindle diameter, respectively. These findings suggest that sexual dimorphism in the muscle spindles of rat medial gastrocnemius is limited to density, which contrasts previous findings reporting differences in extrafusal fibers diameter.